2021
DOI: 10.1063/5.0041148
|View full text |Cite
|
Sign up to set email alerts
|

Smooth, low rate, selective GaN/AlGaN etch

Abstract: The aluminum content is widely used in III-N semiconductors as a determiner of material etch characters. Applications consisting of thin GaN/AlGaN heterostructures can afford a maximum of 6 nm of a thin AlGaN layer over etch demand complex processes with precise low etch rates and low etched GaN surface roughness. In this paper, the effects of bias power and SF6 flow ratios on the chlorine chemistry etch rate, selectivity, and GaN surface roughness are investigated in a high-frequency bias generator and low po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The selectivity in this study is the highest value ever reported, which can be attributed to our systematic optimization and the lowest bias power of our designed etch tool. Additionally, as reported in reference [20], a high selectivity of 33:1 was realized by using a higher frequency bias generator of 40 MHz. The much higher plasma frequency produces lower-energy ions which tends to achieve higher selectivity but with much lower etch rate.…”
Section: Bias Powermentioning
confidence: 99%
“…The selectivity in this study is the highest value ever reported, which can be attributed to our systematic optimization and the lowest bias power of our designed etch tool. Additionally, as reported in reference [20], a high selectivity of 33:1 was realized by using a higher frequency bias generator of 40 MHz. The much higher plasma frequency produces lower-energy ions which tends to achieve higher selectivity but with much lower etch rate.…”
Section: Bias Powermentioning
confidence: 99%